Hubungan Kebiasaan Konsumsi Kopi Dengan Kualitas Tidur Mahasiswa Di Universitas Ichsan Satya Tangerang Selatan - Widhawati, Riswahyuni; Purwanti , Heni; Arpiani, Selsa (STIKes IMC Bintaro, 2023)
Background: Coffee consumption habits are popular among the public, according to data from the ICO reported that domestic coffee consumption in Indonesia from 2014 to 2021 continues to increase. This indication of increasing coffee consumption is characterized by the large growth in the number of modern coffee shops and the variety of coffee products that are in the style of young people in recent years is increasing rapidly. This condition makes the tradition of drinking coffee become increasingly popular among young people, especially college students, but regular consumption of coffee can cause dependence, one of the most obvious negative effects is to make it difficult for a person to sleep, thus this effect can affect the quality of a person's sleep. Objective: to find out whether there is a Relationship between Coffee Consumption Habits and Student Sleep Quality at Ichsan Satya University in 2023. Method: uses a cross-sectional approach with a statistical approach using the chi-square test. The sample of this study was 128 respondents determined by a simple random sampling technique. Results: In terms of the level of coffee consumption habits with a P value of 0.001 which means H0 is rejected, with an OR value (CI: 95%) of 3,907 (1,673-9,123) which means that respondents who have high coffee consumption habits have a poor sleep quality of 3,907 times compared to respondents who consume coffee with low intensity. Conclusion The results of this study show that consuming coffee with high intensity can increase the risk of poor sleep quality. Suggestions It is hoped that it can be used as input to students so that they can limit coffee consumption in a day.